Delivery and Evaluation of the 2012 International Association of Forensic Nurses (IAFN) National Blended Sexual Assault Forensic Examiner (SAFE) Training (UNITED STATES) - Patterson, Debra ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The project sought to address the shortage of sexual assault forensic examiners (SAFE) by delivering and evaluating a comprehensive SAFE training program developed by the International Association of Forensic Nurses (IAFN). To assess if the training was effective, researchers conducted an outcome evaluation using a mixed methods approach, including quantitative pre-post training and qualitative interviews with instructors and students. The evaluation had three main components: 1) to assess training completion, including the percentage of students who completed the training and the factors that contributed to their completion; 2) to ascertain whether students attained knowledge through pre-test/post-tests and the factors that contributed to knowledge attainment; and 3) to determine whether students retained their knowledge using a post-training exam approximately three months following the training, and whether the students incorporated the core concepts of the training into their SAFE practice. The researchers divided the project into 3 studies. Study 1 examined how many students completed the training and what predicted training completion. Study 2a utilized a one-group pre-test post-test design where researchers assessed students' knowledge attainment for 12 online modules. Study 2b utilized a qualitative framework to understand the instructors' pedagogical approach to teaching clinical skills. In addition, researchers conducted qualitative interviews to examine the students' perceptions of the patient care and medical forensic exam skills gained from the clinical component in the SAFE training, and how the clinical training contributed to their skill development. Study 3a explored knowledge retention using an online post-training survey given to students three months following the training. Study 3b utilized the same qualitative framework as Study 2b. Only data for studies 1, 2a, and 3a are available with this collection. The data file has 198 cases and 675 variables. The qualitative interviews for Studies 2b and 3b are not available as part of this data collection at this time.